2021
DOI: 10.1177/00343552211060012
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts Job Quality of Vocational Rehabilitation Consumers Who Are Blind or Have Low Vision?

Abstract: The Workforce Innovation and Opportunity Act emphasizes promoting high-quality, competitive employment for people served by vocational rehabilitation (VR), but few studies have assessed VR consumers’ job quality. The purpose of this study was to investigate job quality and factors that predict the job quality of VR consumers with blindness or low vision (B/LV), taking into consideration their employment status at application. We utilized RSA-911 data of VR consumers with B/LV who were closed in competitive emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…These findings echo previous studies on a snapshot of employment earnings [e.g., 16]. In fact, higher education level (completing high school or college) seemed to consistently lead to higher wages [35,36]. However, models that included training certification/licensure and time-varying limitations as covariates did not fit the data well, suggesting that the effects of these factors on hourly pay over the long term were negligible.…”
Section: Plos Onesupporting
confidence: 85%
“…These findings echo previous studies on a snapshot of employment earnings [e.g., 16]. In fact, higher education level (completing high school or college) seemed to consistently lead to higher wages [35,36]. However, models that included training certification/licensure and time-varying limitations as covariates did not fit the data well, suggesting that the effects of these factors on hourly pay over the long term were negligible.…”
Section: Plos Onesupporting
confidence: 85%
“…While some studies in this theme did utilize RSA-911 data to explore characteristics of VR, 86 , 94 many studies highlighted its limitations. 59 , 86 , 87 , 95 In McDonnall et al’s 86 study, results indicated that job quality indicators were higher for consumers who were employed at application than for those not employed at application.…”
Section: Resultsmentioning
confidence: 99%
“…Findings suggest that disability self-worth may be an important target outcome for clinical settings. McDonnall et al 94 RSA-911 data on people with BVI. N = 8723.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations